TIME MANAGEMENT, SOCIAL SUPPORT, PERSONALITY AND BURNOUT AMONG POSTGRADUATE STUDENTS - Layth, Farah; Mohammed, Mothna; Malik, Shazia; Alrawi, Dhabyan (PEOPLE: International Journal of Social Sciences, 2017)
Time management performs an important role in performing tasks in time without getting any burnout. The purpose of this study was to investigate the relationship of time management, social support, personality and burnout among postgraduate students. In the section of literature review reveals that personality and social support defense the negative effects of time management of burnout. There were 214 respondents who have participated in the online survey consisting of six sections which have work experience, time management, personality, social support, and burnout as their demographic. A descriptive statistics, Pearson Correlation, T-test for Independent Sample Means, and Multiple Regression were used to analyze the data. . There are inconsistencies in the findings obtained by previous researchers on the relationship between time management and burnout among students indicate that research into the effects of time management, personality and social support on students’ burnout is not conclusive. This study attempts to fill the gap by investigating the relationship of time management, social support, personality and to reduce burnout among postgraduate students with proper usage of the skills of time management. Time management has a significant relationship with burnout; however, burnout has no significant relationship with personality were the results of Co-relation statistics.